Pengaruh Gaya Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Karyawan PT Angkasa Pura Support Cabang Jakarta Pusat - Wildan Syifa Arahman; Wiwi Idawati; Feriasi Feriasi (Komunitas Dosen Indonesia, 2023)
This study aims to determine the effect of leadership style and work discipline on employee performance. This study uses 2 independent variables, namely leadership style and work discipline with one dependent variable, namely employee performance. The population in this study were employees of PT Angkasa Pura Support, Central Jakarta Branch. Samples were taken as many as 50 respondents using a saturated sampling technique, namely the sampling technique using a questionnaire.The method in this study used is a quantitative research method. Types and sources of data used are primary and secondary data. Data collection used a questionnaire and library method, the data collected was analyzed using multiple linear regression analysis. In this study, the results obtained were that Leadership Style (X1) had a positive and significant effect on employee performance (Y) at Pt.angkasa pura support, central jakarta branch. This is evidenced by the hypothesis test tcount 5.185 > ttable 0.167 with a significant level (0.000 <0.05). Thus Ho1 is rejected Ha1 is accepted. In this study, the results were obtained that Work Discipline (X2) had a positive and significant effect on Employee Performance (Y) at PT. Angkasa Pura Support Central Jakarta Branch. This is evidenced by the hypothesis test t count 6.692 > t table value 0.167 which is also reinforced by <sig.0.05 or (0.000 <0.05). Thus Ho2 is rejected Ha2 is accepted.In this study it was found that Leadership Style (X1) and Work Discipline (X2) have a positive and significant simultaneous effect on Employee Performance (Y) at PT.Angkasa Pura Support, Central Jakarta Branch. This is evidenced by testing the hypothesis that the value of Fcount is greater than 32. and Ftable (32.> 2.80). With a significant value level of 0.000 <0.05. As well as the coefficient of determination R2 of 0.909 or a simultaneous contribution of 09.1%. Thus Ho4 is rejected and Ha4 is accepted.